Geastrum chamelense (Geastraceae, Agaricomycetes), a new species with setose endoperidium from the tropical dry forest in Jalisco, Mexico - Bautista, Silvia; Raymundo, Tania; Aguirre-Acosta, Elvira; Martínez-González, César Ramiro; Valenzuela, Ricardo (Instituto de Ecología, A.C., 2021)
Background and Aims: Geastrum is characterized by stelliform basidiomata, exoperidium with three layers, sessile or stalked endoperidium, and sulcate, plicate, folded or fibrillose peristome, distinctly or indistinctly delimited, sometimes with mycosclereids. The objective of this study is to describe and illustrate Geastrum chamelense with morphological, ecological and molecular data as a new species from the Chamela Biological Station, Jalisco, Mexico. Methods: Basidiomata collections with different degrees of maturity gathered in 2010 and 2011 from tropical dry forest at the Chamela Biological Station in Jalisco state are described macro- and microscopically. The type material is deposited in the fungal collections of the herbaria ENCB and MEXU. The extraction of DNA, as well as the phylogenetic analyses of ITS, LSU, atp6 and rpb1 sequences, are based on the holotype. Key results: Geastrum chamelense is distinguished by its greyish brown basidiomata, pseudofornicate, fleshy exoperidium, not hygroscopic, sessile endoperidium, subglobose to depressed with peristome plicate, not delimited, and setae present. The latter character is shared with Geastrum setiferum from Brazil, but that species has shorter and wider setae (95-215 × 20-47 µm) than G. chamelense (102-330 × 10.2-15.3 µm). From a phylogenetic perspective, G. chamelense is sister to G. hieronymi and G. cf. calceum, while G. setiferum is not related, as it appears in a separate clade. Conclusions: Geastrum chamelense is recognized as a new species based on morphological, ecological and molecular data.